Effectiveness of Nutrition Booklet to Improve Participation in The Management of Anemia in Cesarean Mothers - Ida Mardalena; Sutejo Sutejo; Eko Suryani (Universitas Muhammadiyah Yogyakarta, 2022)
Background: Severe postpartum anemia after cesarean is strongly associated with predelivery and postpartum Hb levels in maternal. The adverse effects of anemia impact health and economic development. WHO estimates that 12.8% of maternal deaths in Asia can be attributed to anemia.Objective: This study aims to identify the effect of the anemia booklet on the perception, participation, and hemoglobin level of cesarean mothers in the management of anemia.Method: This quasi-experiment with the pre-posttest without control groups design was conducted to measure the effectiveness of education using a nutrition booklet on the level of Haemoglobin and perception variable. 30 respondents were involved, and the data analysis was carried out using a Statistical test using paired t-test with a CI of 95%.Result: The relationship between Hb before and after giving the booklet was revealed with a correlation coefficient of 0.333 and a significance of 0.84 (p-value 0.05). Perceptions before and after understanding the booklet obtained p-value = 0.000 0.05. Management before and after giving the booklet obtained p-value = 0.005 0.05. The interviews found that after receiving information, mothers' perceptions improved regarding understanding anemia, recognizing signs and symptoms, preventing anemia, consuming protein, consuming drinks, and good nutrition for anemia management. After giving anemia management communication through booklets, there was an increase in the mother's participation in consuming snacks, drinking after mealtime, and improving personal and environmental hygiene.Conclusion: Education through booklets affected maternal perceptions and management actions in preventing anemia but did not affect hemoglobin (Hb). It could also increase mothers' perception and participation in consuming snacks, drinking after mealtimes, and personal and environmental hygiene. Furthermore, nurses could use booklets as a medium of counseling.